Assessment of anxiety levels in children aged 4-9 years about the pediatric dentists donning a personal protective equipment during treatment in the COVID-19 pandemic - S Anu; Varun Shetty; Ila Srinivasan; Sabahath Kibriya; Bisma Seher Khan; Sreeraksha Radhakrishnan (Wolters Kluwer Medknow Publications, 2022)
Background: Managing anxiety in children during the pandemic will be a concern for many pediatric dentists. Aim: The aim of this study was to assess the anxiety levels in children aged between 4 and 9 years about the pediatric dentists donning a personal protective equipment (PPE) for dental treatment during the COVID-19 pandemic era in Bengaluru. Materials and Methods: The study was done in two parts with a sample size of 100 each. The first part was a questionnaire-based survey addressed to the pediatric dentists practicing in Bengaluru. The second part of the study was clinical assessment of dental anxiety at three time intervals (T1, T2, and T3) using the animated emoji scale. Results: The study revealed that 87% use preprocedural behavior management post-COVID. Majority of the dentists donned the PPE before conditioning the child (59%) and 41% wore the PPE after conditioning the child. The mean anxiety level in the study children showed an increase in anxiety level at T2 of 3.58 (P < 0.001 ± 1.32) in children aged 4-6 years when compared to T1 and T3 of 3.27 (P < 0.001 ± 1.64) and 3.07 (P < 0.001 ± 1.32), respectively. Conclusion: Children aged between 4 and 6 years showed increased levels of anxiety compared to the 7-9-year age group to the pediatric dentists donning a PPE during treatment in the COVID-19 pandemic. Pediatric dentists also showed a satisfactory knowledge regarding disinfection and fumigation procedures.